Antigen Recognition by MR1-Reactive T Cells; MAIT Cells, Metabolites, and Remaining Mysteries - Corbett, Alexandra J.; Awad, Wael; Wang, Huimeng; Chen, Zhenjun (Frontiers in Immunology, 2020)
Mucosal-associated Invariant T (MAIT) cells recognise vitamin B-based antigens presented by the non-polymorphic MHC class I related-1 molecule (MR1). Both MAIT T cell receptors (TCR) and MR1 are highly conserved among mammals, suggesting an important and conserved immune function. For many years, the antigens they recognise were unknown. The discovery that MR1 presents vitamin B-based small molecule ligands resulted in a rapid expansion of research in this area, which has yielded information on the role of MAIT cells in immune protection, autoimmune disease and more recently in homeostasis and cancer. More recently, we have begun to appreciate the diverse nature of the small molecule ligands that can bind MR1, with several less potent antigens and small molecule drugs that can bind MR1 being identified. Complementary structural information has revealed the complex nature of interactions defining antigen recognition. Additionally, we now view MAIT cells as one subset of a broader family of MR1-reactive T cells (MR1T cells). Despite these advances, we still lack a complete understanding of how MR1 ligands are generated, presented and recognised in vivo. The biological relevance of these MR1 ligands and the function of MR1T cells in infection and disease warrants further investigation with new tools and approaches.